2006
DOI: 10.1186/1467-4866-7-3
|View full text |Cite
|
Sign up to set email alerts
|

Pyrite-induced hydroxyl radical formation and its effect on nucleic acids

Abstract: Background: Pyrite, the most abundant metal sulphide on Earth, is known to spontaneously form hydrogen peroxide when exposed to water. In this study the hypothesis that pyrite-induced hydrogen peroxide is transformed to hydroxyl radicals is tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(109 citation statements)
references
References 45 publications
8
97
0
4
Order By: Relevance
“…Several components in the SLF may be influencing the relative rates of the two hydrogen peroxide decomposition reactions through complexation of dissolved iron. Earlier work has shown that hydrogen peroxide can be stabilized in pyrite slurries by adding EDTA, a strong Fe(II) chelator (Cohn et al 2006c). Citrate, which is present in SLF used here, also forms strong complexes with ferrous iron.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several components in the SLF may be influencing the relative rates of the two hydrogen peroxide decomposition reactions through complexation of dissolved iron. Earlier work has shown that hydrogen peroxide can be stabilized in pyrite slurries by adding EDTA, a strong Fe(II) chelator (Cohn et al 2006c). Citrate, which is present in SLF used here, also forms strong complexes with ferrous iron.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, a study conducted in Great Britain showed that tissue recovered from pneumoconiotic lungs of deceased coal miners has abnormally high amounts of iron-enriched material (Bergman and Casswell 1972), consistent with the notion that exposure to iron minerals associated with coal plays a role in the pathogenesis of CWP. Pyrite and pyritebearing coal have recently been shown to spontaneously generate ROS when placed in water (Cohn et al 2005(Cohn et al , 2006c. On the basis of these results and additional research with pyrite-bearing coal, it has been suggested that the inhalation of iron-bearing dust may be responsible for a chronic elevated level of reactive oxygen species (ROS) production in lung tissue.…”
mentioning
confidence: 95%
“…The formation of these reactive oxygen species (ROS) also explains the recent observation that aqueous pyrite slurries degrade yeast RNA, ribosomal RNA, and DNA (Cohn 2006). Pyrite is thought to form H 2 O 2 through the iron-catalyzed Haber-Weiss reactions.…”
Section: Health Considerationsmentioning
confidence: 96%
“…The formation of these reactive oxygen species (ROS) also explains the recent observation that aqueous pyrite slurries degrade yeast RNA, ribosomal RNA, and DNA (Cohn et al 2006). Pyrite is thought to form H 2 O 2 through the Fe-catalyzed Haber-Weiss reactions.…”
Section: Study Of Elements and Mineralsmentioning
confidence: 96%